Exploring the Bioavailability of Red Grape Skin Extract Polyphenols: A Caco-2 Cell Model Study - Edurne Elejalde; Rosa María Alonso; María Carmen Villarán; Lucía Díez-Gutiérrez; María Chávarri; Iratxe López-de-Armentia (Foods, 2025)
Grapes are a rich source of polyphenols with a positive impact on human health. Polyphenols need to be bioavailable to exert any beneficial effect. However, there is limited knowledge on the bioavailability of polyphenols in grape extracts. The intestinal permeability of nine polyphenols of a red grape skin extract (GSE) was investigated using the Caco-2 cell model that simulates the human intestinal epithelium: three anthocyanins (delphinidin-3-O-glucoside, petunidin-3-O-glucoside and malvidin-3-O-glucoside), three flavonols (quercetin-3-glucoside, kaempferol-3-galactoside and kaempferol-3-glucoside), two hydroxybenzoic acids (gallic acid and syringic acid) and one hydroxycinnamic acid (caftaric acid). Two concentrations of GSE (15 mg/mL and 22 mg/mL) were used. The transport efficiency (TE) through the Caco-2 monolayer was studied. Among anthocyanins, only malvidin-3-O-glucoside was detected at the basolateral side, which represents the bloodstream, with a TE of 1.08 ± 0.01%. Flavonols resulted in a variety of results depending on the GSE concentration. Among flavonols, kaempferol-3-glucoside showed the highest TE of 130 ± 3%. Gallic acid showed the highest TE among the investigated polyphenols with 188 ± 3%. This study provides data on the intestinal transport of red grape skin extract polyphenols that can be used to explore the underlying mechanisms of the intestinal absorption and the bioactivity of natural grape extracts.